ANALISIS KEPUASAN PENGGUNA TERHADAP KUALITAS PELAYANAN JALAN TOL MENGGUNAKAN METODE IPA - Amanah, Rizka; Eva Azhra Latifa (Construction and Material Journal, 2025)
Sheikh Mohammed bin Zayed Road (MBZ), formerly known as Jakarta-Cikampek Road (Elevated) and managed by PT. Jasa Marga, is a barrier-free road that must meet service quality standards to ensure user comfort and safety. The study aimed to analyze the satisfaction of 100 respondents using the Importance Performance Analysis (IPA) method. The results of the study showed a 92.05% correlation between interest levels and performance, indicating less satisfactory road performance. The Cartesian diagram identifies a critical service attribute with the highest average score as the available and clearly visible road security fence (4.36), while the less important attributes are officers being friendly and polite when on duty (3.94). For performance, the attribute with the greatest score is a clear sign before entering a curve; the user feels safe (4.77), whereas the attributes with the lowest score are convenient toll road surfaces when crossing (roads are considered flat and non-wavelets, so speed does not decrease) (3.02). Attributes included in the Key Priority Quadrant are convenient toll road surfaces when crossing (roads are considered flat and non-wavelets, so speed does not decrease), which require solutions such as routine inspection and maintenance, better paving technology, periodic resurfacing, and strict quality control.